Trace Element Analysis of Red-rot Disease Incidence in Sugarcane by Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES) - Raja Kumar, N.; Narayanaswamy, R. (Asian Journal of Chemistry, 2016)
An attempt has been made to detect and estimate some important macro and micro elements present in both resistant and red-rot disease infected sugarcane of different varieties using inductively coupled plasma atomic emission spectrometry. This analysis reveals the presence of trace elements like B, Na, Mg, K, Ca, Cr, Mn, Fe, Co, Ni, Cu and Zn. A possible correlation between the status of trace elements and the diseased condition of sugarcane has been attempted.